IMPACT OF DISORDER ON THE QUANTUM STATES OF TWO PHOTONS GENERATED IN NONLINEAR WAVEGUIDE ARRAYS - Rojas-González, Edgar A. (2026)
In an array of nonlinear waveguides, quantum states can be generated from classical states through spontaneous parametric down-conversion of photons. This work simulates and analyzes the effect of disorder on light propagation and its quantum correlations, implementing disorder in three system parameters: coupling, injection amplitude, and injection phase. It is determined that when light is injected into only one waveguide, disorder in the coupling increases localization and reduces dispersion. Moreover, in this case, propagation tends to remain ballistic, a characteristic feature of waveguide arrays. Conversely, disorder in the injection amplitude and phase tends to delocalize the wave function, with the latter having a more pronounced effect. Finally, it is observed that quantum correlations, obtained from the correlation matrix, are robust in the presence of disorder, particularly the null elements.